Variation of Plasma Pressure at the Auroral Oval Latitudes Before, During, and After the Isolated Geomagnetic Substorm on December 22 2008 - Stepanova, M (Pleiades Publishing, 2020)
Abstract: The change in plasma pressure at the latitudes of the auroral oval before, during, and after the isolated geomagnetic substorm on December 22, 2008, were studied using data from the F13, 15, 16, and 17 DMSP satellites. One feature of the studied event was a long period of values of AL index that were close to zero. During this time, there was a more than double increase in the dynamic pressure of the solar wind. The projection of pressure maxima on the equatorial plane was carried out using models of the geomagnetic field and a model of the pressure distribution in the equatorial plane. It was shown that the maximum plasma-pressure values at the latitudes of the auroral oval increase with increasing dynamic pressure of the solar wind during the magnetically quiet period to substorm. The maximum values of the plasma pressure for the studied period are recorded during the expansion phase of the substorm. A decrease in the solar-wind dynamic pressure to values close to the values during the magnetically quiet time before the substorm was not accompanied by a drop in the plasma pressure after the substorm. The difference between the plasma pressure dynamics during an isolated substorm and the pressure dynamics during a substorm taking place during magnetic storm is discussed. © 2020, Pleiades Publishing, Ltd.